THE INFLUENCE OF EDUCATION AND ENTREPRENEURIAL CULTURE ON ENTREPRENEURIAL INTENTION WITH MINDSET AS A MEDIATION VARIABLE IN STUDENTS AT TARUMANAGARA UNIVERSITY - Muhammad Denis Mahyusa1; Andi Wijaya (Graduate Program of Universitas Tarumanagara, 2026)
Indonesia’s entrepreneurship ratio, which remains at only 3.47%, presents a significant challenge in reducing unemployment, particularly among university graduates. This study aims to examine the impact of entrepreneurship education and entrepreneurial culture on the entrepreneurial mindset and intentions of students at Tarumanagara University, as well as to assess the mediating function of entrepreneurial mindset. A survey method was applied involving 116 active students, with data collected through an online questionnaire. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The findings indicate that entrepreneurship education exerts a positive yet insignificant effect on both entrepreneurial mindset and entrepreneurial intention. Entrepreneurial culture shows a positive and significant influence on entrepreneurial mindset, although its effect on entrepreneurial intention is not significant. Furthermore, entrepreneurial mindset positively and significantly affects entrepreneurial intention and acts as a significant mediator between entrepreneurial culture and entrepreneurial intention, but does not mediate the relationship between entrepreneurship education and entrepreneurial intention. These results highlight the importance of strengthening entrepreneurial culture and nurturing entrepreneurial mindsets within the university environment to enhance students entrepreneurial intentions.